Combined control of a flywheel energy storage system and a vanadium redox flow battery for wind energy applications in microgrids - Suvire, Gaston Orlando (2017)
The incorporation of wind generation in microgrids is growing progressively. This integration can introduce problems in the dynamics and power quality of the electrical system due to the wind fluctuations. This work proposes a controller composed by a power conditioning system (PCS), a Flywheel Energy Storage System (FESS) and a Vanadium Redox Flow Battery (VRFB) to palliate problems introduced by wind generation in microgrids. A model of the PCS/FESS-VRFB controller is presented and a method to control the power exchanged between the controller and the power system is suggested. The control method has two modes, namely: power levelling and frequency control. The performance of the PCS/FESS-VRFB controller is studied when it works with wind power generation in the microgrid through simulation tests. Results demonstrate suitable performance of the control methods and high effectiveness to level the wind power fluctuations and to provide support to the frequency control of the microgrid.